(untitled) (Research, Society and Development, 2021)
This work aims to investigate jargonaphasia reversibility during the language learning process. Thus, initially, we explored the concepts developed about jargonaphasia. For this, we show that it is necessary to understand that jargon is a phenomenon that goes beyond speech therapy, constituting a multidisciplinary field of study that also encompasses neurology, medicine, philosophy, and the language sciences. Furthermore, it appears that the study of jargonaphasia requires the speech therapist to be a polymath, seeking information that, although related to speech therapy, constitutes areas of examination independent of it. The central methodology used to investigate the proposed objectives was the narrative bibliographic review, seeking parameters and criteria in the works of authors who had previously studied the proposed theme.